Baseline factors associated with death in a COVID-19 hospital cohort, Sao Paulo, 2020 - Thais Claudia Roma de Oliveira Konstantyner; Camila Bertini Martins; Carla Gianna Luppi; Suely Miyuki Yashiro; Nívia Aparecida Pissaia Sanches; Frederico Molina Cohrs; Paulo Abrão Ferreira; Eduardo Alexandrino Medeiros (Universidade de São Paulo, 2021)
ABSTRACT This study aimed to verify socio-demographic and baseline clinical factors associated with death in a hospital cohort of patients with COVID-19. A retrospective cohort study was conducted between February and December 2020 in a university hospital in the city of São Paulo, using Hospital Epidemiology Center data. RT-PCR-positive patients were selected to compose the sample (n = 1,034). At the end of the study, 362 (32%) patients died. In this cohort, age equal to or greater than sixty years (HR = 1.49) and liver disease (HR = 1.81) were independent risk factors for death from COVID-19 associated with higher in-hospital mortality.